Fetal down syndrome: determining the risk based on fetal-specific DNA methylation ratio - Zainuddin, Norafiza; Mohd. Ridah, Lailatul Jalilah; Abdul Ghafar, Nurul Fatehah; Roslani, Anna Liza; Ismail, Rozihan; Muhammad, Siti Aeshah @ Naznin (The International Institute of Knowledge Management (TIIKM), 2019)
Non-invasive prenatal diagnosis has becoming popular in determining the risk of genetic abnormalities in unborn babies, particularly Down Syndrome (trisomy 21). In this research, methylated DNA immunoprecipitation (MeDIP)-real time quantitative PCR (qPCR) method based on differentially methylated regions (DMRs) or methylation differences between mother and fetus has been employed. Circulating cell free DNA (ccfDNA) was extracted from 28 plasma specimens of pregnant women recruited from January 2017 to February 2019 in Kuantan, Pahang. Seven out of 28 subjects were grouped as high risk (probable trisomy) cases referring to the nuchal translucency reading. The extracted ccfDNA was then sheared and subjected to MeDIP-qPCR. Three DMRs namely EP1, EP7 and EP10 were chosen from previous research to be analyzed, along with hypermethylated and hypomethylated controls. At the moment, Cq values have been obtained for a number of samples and normalization of the raw data will be carried out as normalization of PCR reactions and normalization based on the real-time qPCR primer’s efficiency. The non-invasive prenatal detection of trisomy 21 will be achieved by determining the methylation ratio of normal and trisomy 21 cases for each tested fetal-specific DMR present in the maternal peripheral blood, followed by further statistical analysis. It is hoped that by the end of this study, the risk of fetal Down syndrome can be confirmed and tabulated for all high risk samples.